Foraging and habitat use of common duikers, Sylvicapra grimmia, in a heterogeneous environment within the Soutpansberg, South Africa. (25th October 2013) - Abu Baker, Mohammad A.; Brown, Joel S.
Abstract We investigated aspects of the foraging behaviour and activity patterns of free‐ranging common duikers (Sylvicapra grimmia) within the Soutpansberg, South Africa. We used giving‐up densities (GUD) and camera traps to test for habitat selection and patch‐use behaviour by common duikers inhabiting a grassland containing distinct 'islands' of woody vegetation. Foraging in or around a wooded island was affected by its surrounding vegetation. GUDs were significantly lower in portions dominated by tall grass and scattered ferns and highest in areas with open short grass and thick fern. Using grids of 5 × 5 stations, we mapped the duikers' foraging on a larger scale that incorporated neighbouring rocky hillsides. The duikers preferred feeding in areas with tall grass and scattered fern (sufficient cover and escape routes), followed by the wooded islands and thick fern (lack of sightlines/escape routes and presence of predator‐ambush sites), whereas little foraging occurred at the edges and rocky areas (hard substrate that impede escape potential). Photos (total 873) revealed solitary activity, highest in the late afternoon. Photos of vigilant individuals were mostly from rocky and fern habitats. Our results suggest that the duikers allocated their feeding efforts, activity and vigilance patterns to attune to their perceived risk of predation within their heterogeneous environment.